The SQE and creativity: a race to the bottom?. Issue 4 (2nd October 2018) - Morrison, Doug
ABSTRACT: This paper explores the use of assessment methods in law modules which explicitly value and encourage creativity and innovation. It does so in the context of the Solicitors Qualifying Examination (SQE) and argues that the type of learning and teaching likely to be promoted by this "Super Exam" is the exact opposite of the deep learning and critical thinking that higher education should foster. The paper draws on some of the recommendations of the Legal Education and Training Review (LETR) and a service review evaluating the introduction of poster presentations as a replacement for a multiple-choice question (MCQ) test as an assessment method into the Medical Law module at Leeds Beckett University and highlights the value of encouraging creativity in order to foster a wide variety of valuable skills.